2017
DOI: 10.1038/srep46173
|View full text |Cite|
|
Sign up to set email alerts
|

The presence of microplastics in commercial salts from different countries

Abstract: The occurrence of microplastics (MPs) in saltwater bodies is relatively well studied, but nothing is known about their presence in most of the commercial salts that are widely consumed by humans across the globe. Here, we extracted MP-like particles larger than 149 μm from 17 salt brands originating from 8 different countries followed by the identification of their polymer composition using micro-Raman spectroscopy. Microplastics were absent in one brand while others contained between 1 to 10 MPs/Kg of salt. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
263
2
10

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 391 publications
(295 citation statements)
references
References 52 publications
3
263
2
10
Order By: Relevance
“…Studies have also investigated the potential harms of micro‐ and nano‐plastics found to be widely dispersed in tap and bottled water, table salt, and fish (Harvey and Watts ; Karami et al. ; Kosuth et al. ; Prata ; Rist et al.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have also investigated the potential harms of micro‐ and nano‐plastics found to be widely dispersed in tap and bottled water, table salt, and fish (Harvey and Watts ; Karami et al. ; Kosuth et al. ; Prata ; Rist et al.…”
Section: Methodsmentioning
confidence: 99%
“…S2) and size (from μm to mm). Moreover, with different plastic materials, aspects of the mass change vary, including stiffness (H), thickness (x), anisotropy (y), the density of plastic materials (ρ) 17 . The static electricity of the charged microplastics is another factor that should be considered, because it might lead to a high airborne proportion of microplastics.…”
Section: Resultsmentioning
confidence: 99%
“…Microplastics sources are generally categorised as (i) primary sources of microplastics produced directly in industry 16 and (ii) secondary microplastics generated indirectly from the fragmentation of larger plastic residues. Karami, et al 17 called microplastic the chief cross-border contaminant due to their low density and high durability. Once introduced into the environment, the fate and transportation of microplastics can be fuelled through wind advection, stormwater runoff, drainage systems and wastewater 18 .…”
mentioning
confidence: 99%
“…The presence of microplastics in products available for consumption by humans raises dietary concerns. Microplastics have been reported in beer and honey (Liebezeit & Liebezeit, 2014), as well as in table salt Karami et al, 2017), but most reports focus on microplastic presence in seafood (EFSA, 2016;FAO, 2017).…”
Section: Invertebratesmentioning
confidence: 99%